一种基于视觉认知功能损害的精神性疾病检测装置 (2024)
本发明涉及一种基于视觉认知功能损害的精神性疾病检测装置，包括：图形显示模块、反馈模块、数据处理模块和诊断终端；图形显示模块用于显示若干项视觉认知功能检测对应的图像；反馈模块根据图像提出问题或提供备选项，并获取被试对问题的回答；数据处理模块用于对反馈模块获取的与各项视觉认知功能检测对应的回答进行打分；将数据处理模块获得的分值代入诊断终端中经过诊断模型，根据各项视觉认知功能检测对应的分值判断被试的精神性疾病类型。其能够更加准确的判断基于视觉认知功能损害的神经性疾病的类型，使检测结果更加客观，降低了误诊的概率。 The invention relates to a mental disease detection device based on visual cognition impairment. The mental disease detection device comprises a graphic display module, a feedback module, a data processing module and a diagnosis terminal. The graphic display module is used for displaying images corresponding to the detection of various visual cognition functions; the feedback module puts forward questions or provides alternative items according to the images, and obtains answers of a subject to the questions; the data processing module is used for scoring the answers which are acquired by thefeedback module and correspond to the detection of each visual cognition function; and the scores obtained by the data processing module are put into the diagnosis termi